A Review on Indian Sago Starch And Its Pharmacuetical Applications (International Journal of Pharmaceutical and Life Sciences, 2013)
Indian sago starch extracted from Tapioca roots finds its application not only as a food but also numerous commercial applications. In the present review we are discussing concisely the extraction, physiochemical properties, chemical modifications and pharmaceutical applications of Indian sago starch. The sago starch is a cheap, easily available, biodegradable and a versatile polymer. Starch has always been an important excipient in the pharmaceutical industry. It is conventionally used as a binder, disintegrant, diluent, granulating agent. It is also a starting material for many other chemicals like ethanol, glucose and cyclodextrin. Several modifications were attempted on native starch to improve and modulate its physiochemical properties. DOI: http://dx.doi.org/10.3329/ijpls.v2i3.15456 International Journal of Pharmaceutical and Life Sciences Vol.2(3) 2013: 99-106